How Informative Is Floating NAV When Securities Trade Infrequently?. Issue 1 (February 2016) - Allen, Kyle D.; Cashman, George D.; Winters, Drew B.
Abstract: We examine if a floating net asset value (NAV) increases the transparency of risk for investors. Using closed‐income fixed income funds we find little evidence that a floating NAV helps investors better understand the value and risk of a fund when a fund's assets trade infrequently. This potentially informs the debate regarding the adoption of a floating NAV in the money market industry. Our results suggest that it is unlikely that the benefits of floating NAV will outweigh the costs.